Transitivity Analysis on The Portrayals of Indonesian Police Image by The Jakarta Post And The Sydney Morning Herald in Ferdy Sambo Case - Lenora, Siska Ria; Tania, Yushellia; Tunardi, Elisa Adveny (Journal of Language and Literature, 2023)
The image of the police has become a topic of intense public interest, largely due to the extensive media coverage they have received, with the recent case involving Sambo serving as the latest example. The present study looks at how a local media, The Jakarta Post, and an international media, The Sydney Morning Herald, reported the case. The study utilized Critical Discourse Analysis as a research method, with a specific focus on analyzing the transitivity structures of both news articles to find similarities and differences in their depictions of the Indonesia’s Police Force. The result of the analysis showed that both news articles used Material processes considerably yet with a different focus on the participants. The Jakarta Post placed the police as Actor and thus acknowledged its authoritative role in resolving the case. Meanwhile, The Sydney Morning Herald presented the case as Actor and downplayed the presence of the police by employing a frequent usage of passive sentences. It was found through analysis of the Verbal process that both news articles utilized almost equal numbers of statements from related sources. However, The Jakarta Post put the police mainly as Sayer while The Sydney Morning Herald only used one statement from the police in their report.